Perceived Freedom of Expression at New Zealand Universities - Jamin Halberstadt; Arindam Basu; Barry Hughes; Ruth Hughes; Michael Johnston; James Kierstead; David Rozado (Social Sciences, 2022)
Few topics are currently as polarizing as the appropriate limits, and perceived dangers, of free speech on university campuses. A side effect of this polarized environment is that students themselves may be reluctant to speak publicly on politically sensitive topics. Indeed, recent surveys by the Heterodox Academy (HxA) revealed that a majority of American university students thought their campus was not conducive to the free expression of ideas, and a substantial minority were personally reluctant to discuss “hot topics” like politics or sexual orientation in class. To see whether these results are uniquely American phenomena, we reran the HxA’s survey on 791 students, recruited via advertisements, enrolled in New Zealand universities. As in the original survey, participants answered questions, administered online, about their comfort sharing their opinions on issues related to gender, politics, religion, and sexual orientation, as well as their estimates of other groups’ discomfort. Despite significant sociopolitical differences between the two countries, our results, generally speaking, bear out those in the United States. In both countries, politics elicited the most reluctance to speak, followed by religion, and then gender and sexual orientation (which were equivalent), and New Zealanders were more reluctant than Americans to speak on the latter two topics. Other similarities and differences between the two data sets are discussed, but it is clear that chilled campus speech is not confined to the United States.